The effect of exclusive breastfeeding education using audio-visual media and e-booklets on pregnant women’s knowledge and attitude toward providing exclusive breastfeeding - Nurfajrillah, Trisna; Nurhayati, Eka; Fatimah, Fatimah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: According to international child feeding guidelines, the rich nutrient content of breast milk makes it an ideal food for infants and young children. Breastfeeding education in community health centers is only given once during pregnancy in integrated antenatal care. Therefore, additional intervention is needed by mothers to increase their knowledge and attitude about breastfeedingObjectives: This study aims to identify the effect of exclusive breastfeeding education through audio-visual media and booklets on the knowledge and attitudes of pregnant women on their third trimester toward providing exclusive breastfeeding.Methods: This study is a quantitative method with a quasi-experimental a non-equivalent control group design. The study included 60 third-trimester pregnant women for the intervention group and control group, who met the inclusion and exclusion criteria. The intervention involved providing booklets and audio-visual materials to the experimental group, while the control group was only given booklets. Mother's knowledge and attitude was measured using a questionnaire. The data were analyzed using a Paired t-test.Results: This study indicated a significant difference in the knowledge and attitudes of respondents before and after education using audio-visual media and booklets in the control and experimental groups with a p-value 0.000 <0.05.Conclusions: Exclusive breastfeeding education using audio-visual media and booklets had an effect on mothers' knowledge and attitudes towards exclusive breastfeeding. There is standardize education about breastfeeding at least two times in addition to integrated antenatal care visits to increase knowledge and attitude towards breastfeeding.